Tinnitus and hyperacusis in autism spectrum disorders with emphasis on high functioning individuals diagnosed with Asperger's Syndrome. Issue 10 (October 2015) - Danesh, Ali A.; Lang, Dustin; Kaf, Wafaa; Andreassen, William D.; Scott, Jack; Eshraghi, Adrien A.
Abstract Objectives To evaluate the prevalence of tinnitus and hyperacusis in individuals with Asperger's Syndrome (AS). Methods A home-developed case-history survey and three item-weighted questionnaires: Tinnitus Reaction Questionnaire (TRQ), Tinnitus Handicap Inventory (THI), and the Hyperacusis Questionnaire (HQ) were employed. These tools categorize the subjective response to tinnitus and hyperacusis. The research tools were mailed to a mailing list of individuals with Asperger's Syndrome. Results A total of 55 subjects diagnosed with AS were included in the analysis (15.5% response rate). Sixty-nine percent of all respondents (38/55) reported hyperacusis with an average HQ score of 20.7. Furthermore, 35% (19/55) reported perceiving tinnitus with average scores of 27 for the TRQ and 23 for the THI. Thirty-one percent (17/55) reported both hyperacusis and tinnitus. The prevalence of hyperacusis in the AS respondents remained relatively constant across age groups. Conclusions Hyperacusis and tinnitus are more prevalent in the ASD population subgroup diagnosed with AS under DSM-IV criteria than in the general public. Hyperacusis also appears to be more prevalent in the AS population than in the ASD population at large. Future research is warranted to provide insight into the possible correlation between tinnitus and hyperacusis symptoms and the abnormal social interactions observed in this group.